2023
DOI: 10.21070/perisai.v7i2.1663
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Factors That Influence The Perceptions of Culinary Business Owners Regarding Intention to Register For Halal Certificates

Khaerud Dawam,
Andi Iswandi

Abstract: Indonesia Law No. 33 of 2014 concerning Halal Assurance requires that by 2019 halal certification should be effectively implemented for food and beverage products, as well as service products related to both. Out of the 1.6 million micro, small, and medium enterprises (MSMEs), only 10 percent have been halal certified. This study aims to analyze the factors that influence the perceptions of culinary business owners regarding intention to register for halal certificates. Theory of Planned Behavior will be modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Based on the results of community service activities, it can be concluded that halal certification literacy for MSME business actors in the Sipirok Market Branch is still relatively low. certification literacy for MSME business actors is very necessary to support the development of their businesses (Dawam & Iswandi, 2023;Pratikto et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%
“…Based on the results of community service activities, it can be concluded that halal certification literacy for MSME business actors in the Sipirok Market Branch is still relatively low. certification literacy for MSME business actors is very necessary to support the development of their businesses (Dawam & Iswandi, 2023;Pratikto et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%